2015
DOI: 10.1177/2045125314566807
|View full text |Cite
|
Sign up to set email alerts
|

Use of automated medication adherence monitoring in bipolar disorder research: pitfalls, pragmatics, and possibilities

Abstract: Automated devices such as MEMS can assist investigators in evaluating adherence in patients with BD. Knowing the anticipated pitfalls allows study teams to implement preemptive procedures for successful implementation in BD adherence studies and can help pave the way for future refinements as automated adherence assessment technologies become more sophisticated and readily available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 30 publications
0
42
0
1
Order By: Relevance
“…Although the use of such monitors has the potential for increasing the reach of AEIs, the available devices remain relatively cost pro-C l i n i c a l r e s e a r c h hibitive for individuals with serious mental illness and for public mental health systems. 26 Also, it is not entirely clear from the available studies if the observed benefits of electronic monitors can be achieved only when they are used in combination with other supports-eg, a case worker who intervenes when problems with adherence arise-which would add to the costs and complexity of the deployment of these devices. Also, in some cases medications must be transferred to the electronic dispensers by the individuals themselves, who may have cognitive or motivational difficulties in repeatedly completing this task, prefer traditional medication containers or pill boxes, or require childproof containers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of such monitors has the potential for increasing the reach of AEIs, the available devices remain relatively cost pro-C l i n i c a l r e s e a r c h hibitive for individuals with serious mental illness and for public mental health systems. 26 Also, it is not entirely clear from the available studies if the observed benefits of electronic monitors can be achieved only when they are used in combination with other supports-eg, a case worker who intervenes when problems with adherence arise-which would add to the costs and complexity of the deployment of these devices. Also, in some cases medications must be transferred to the electronic dispensers by the individuals themselves, who may have cognitive or motivational difficulties in repeatedly completing this task, prefer traditional medication containers or pill boxes, or require childproof containers.…”
Section: Discussionmentioning
confidence: 99%
“…25 Practically, the devices are often too bulky to keep on one's person and separate dispensers are needed to accommodate polypharmacy. 26 These and other characteristics of these devices limit their current utility in regular clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, our method of identifying an index BD drug adherence based upon dosing frequency and most recent start date appeared to show that the index BD drug adherence was very tightly correlated with overall/average BD drug adherence. How to best measure medication adherence in BD, where use of multiple drugs is the norm, has yet to be definitely determined . An advantage of identifying an index/single drug to track for adherence, as was done in this study, is that this allows comparison with automated pill monitoring using MEMS.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence in SMI is very poor; estimated non-adherence rates for people diagnosed with schizophrenia range from 40 to 75 % [ 6 , 7 ]. Studies have found that 75 % of people with chronic schizophrenia discontinue their medication within 18 months [ 8 ] and non-adherence rates in bipolar disorder range between 20 and 60 % with a mean of 41 % [ 9 , 10 ]. Antipsychotic prescribing lends itself to SDM, because the adverse event profile is the main factor in the choice of antipsychotics [ 11 ].…”
Section: Introductionmentioning
confidence: 99%